2017 46th International Conference on Parallel Processing (ICPP) 2017
DOI: 10.1109/icpp.2017.9
|View full text |Cite
|
Sign up to set email alerts
|

Preparing HPC Applications for the Exascale Era: A Decoupling Strategy

Abstract: Production-quality parallel applications are often a mixture of diverse operations, such as computation-and communication-intensive, regular and irregular, tightly coupled and loosely linked operations. In conventional construction of parallel applications, each process performs all the operations, which might result inefficient and seriously limit scalability, especially at large scale. We propose a decoupling strategy to improve the scalability of applications running on large-scale systems. Our strategy sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…We are starting to quantify the benefits of the individual features sets of the SAGE stack in the ongoing process of providing a holistic picture of the benefits of the SAGE architecture for Exascale. On that front, we present the performance results of two components of the high-level HPC interfaces for the SAGE platform: the PGAS I/O using MPI storage windows [30] and MPI streams [32,31,16] for post-processing and efficient parallelI/O operations, exploiting the SAGE architecture. This aims to provide introductory results for SAGE stack components with results for other components targeted for future works.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We are starting to quantify the benefits of the individual features sets of the SAGE stack in the ongoing process of providing a holistic picture of the benefits of the SAGE architecture for Exascale. On that front, we present the performance results of two components of the high-level HPC interfaces for the SAGE platform: the PGAS I/O using MPI storage windows [30] and MPI streams [32,31,16] for post-processing and efficient parallelI/O operations, exploiting the SAGE architecture. This aims to provide introductory results for SAGE stack components with results for other components targeted for future works.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, our work in SAGE focuses on parallel streams, where data producers and consumers are distributed among processes that require communication to move data. To achieve this, we have developed a stream library, called MPIStream, to support post-processing and parallel I/O operations on MPI consumer processes [31,16]. More details about MPI streams operation semantics and MP-IStream implementation are provided in Ref.…”
Section: High-level Hpc Interfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the irregular nature of certain input datasets, these design considerations pose performance restrictions when the workload per process becomes unexpectedly unbalanced. In such cases, it has been demonstrated that the use of decentralized algorithms can provide significant performance benefits [14].…”
Section: Introductionmentioning
confidence: 99%